Hans Namuth and Georg Reisner, war photographers (1936-1939): analysis, identification and assessment of the film negatives found at National Library of Spain - Vega Hidalgo, Carlos; García Fernández, Laura (Revista General de Información y Documentación, 2023)
The German photographers Hans Namuth and Georg Reisner documented the scenes of the Spanish Civil War from July 1936 to March 1937. Their images occupied the pages of the most important international newspapers and illustrated magazines, however, their professional work has received less recognition compared to that made by other reporters with whom they shared the same moments and places during the contest in Spain. The origin of this research lies in the discovery and identification of a group of 6x6 format film negatives attributed to Hans Namuth and Georg Reisner integrated among the photographic materials of the Commissariat de Propaganda commissioned by the Government of Catalonia and preserved in the National Library of Spain. In the process of contextualizing the material, the first gaps in knowledge about the photographic work of this tandem of reporters and the subsequent verification of the lack of rigorous studies that globally address their trajectory before, during and after their time in Spain. The analysis, identification and evaluation of photographic documentation allows the work of photojournalists to be studied from multiple perspectives, as well as opening new lines of research on their biographies and photographs taken in Spain between 1936 and 1937.
Keywords: Hans Namuth; Georg Reisner; Spanish civil war; Photojournalism; Photographic documentation; Photography